Ignatius MacFarland : frequenaut! - Feig, Paul (Little, Brown Books for Young Readers, 2008)
Bullied in school and called "Piggy MacFartland," twelve-year-old Iggy longs to travel to another planet and live among extraterrestrials, until an explosion transports him to a scary alternate reality.